Identificação de microproteínas codificadas por pequenas ORFs em mycolicibacterium smegmatis (mycobacterium smegmatis) por meio de análise proteogenômica - Dalberto, Pedro Ferrari (2021)
Tuberculosis is an infectious disease mainly caused by Mycobacterium tuberculosis. Despite the availability of treatment and vaccine, this disease accounts for millions of deaths annually. Moreover, the emergence of resistant strains to the first-line drugs is increasing. Therefore, the understanding of mycobacterial biology is essential to the development new therapeutic strategies to reduce the tuberculosis incidence in the world. Since the first prokaryotic DNA sequencing twenty-five years ago, it has become possible to delve deeper into bacterial genomes and to better understand the organization and regulation of their genes. Traditionally, annotation pipelines only include in their workflow Open Reading Frames (ORFs) with at least 300 nucleotides, or 100 codons. Hence, the set of ORFs with less than 100 codons, known as small ORFs (smORFs), is excluded by an arbitrary cutoff since countless smORFs sequences may be found in any genome just by chance, with a high probability of being biologically meaningless and not, in fact, a coding sequence. In this work. We investigated the hidden universe of microproteins encoded by smORFs in Mycolicibacterium smegmatis mc²155 (Mycobacterium smegmatis), normally used as a model of M. tuberculosis due to its non-pathogenic and fast-growing characteristics, by applying a proteogenomic approach. Combining genomics, transcriptomics and proteomics we were able to accurately identify and annotate these smORFs. We improved the results performing different methods to enrich low molecular weight proteins, as they may have low abundance in a complex biological sample. Throughout our analysis, we identified 16 unannotated ORFs, one of which has 23 paralogues spread across copies of IS1096, a well-known M. smegmatis transposon, showing that element encodes a total of three ORFs, one more than previously reported. Our workflow also allowed us to extend the sequence of a previously annotated protein and to find the shortest ORF yet in the genome of M. smegmatis. We were able to show that the most prominent start codon in these sequences is GTG, followed by the canonical ATG and the alternatives ATT and TTG. Many of these new ORFs have both annotated and unannotated orthologous sequences in Mycobacteria and other close bacteria. Moreover, we showed how the combination of multiple proteomes can properly exclude known proteins that would otherwise be deemed as novel. We expect this study to contribute to the understanding of mycobacterial genomes and proteomes. Moreover, we believe that the discovery of these proteins will provide insights for new studies dedicated to their structures, functions, and essentiality.